Village Political Economy, Land Tenure Insecurity, and the Rural to Urban Migration Decision: Evidence from China. (19th December 2017) - Giles, John; Mu, Ren
Abstract: This article investigates the impact of land tenure insecurity on the migration decisions of China's rural residents from 1995 to 2003. The article appeals to a simple model to frame the relationship between migration and the probability that a reallocation of land in the village will occur in the following year. Empirically, the article first demonstrates that a village leader's support for an administrative land reallocation carries with it the risk of losing a future election. Exploiting election timing and village heterogeneity in lineage group composition, the article identifies the effect of reallocation risk on migration decisions. In response to an expected land reallocation in the following year, the probability that a rural resident migrates out of the county declines by 2.4 percentage points, which accounts for 15% of the annual share of village residents, aged 16 to 50, who worked as migrants during the period. This finding underscores the potential importance of secure property rights for facilitating labor market integration and the movement of labor out of agriculture.